Clinical Presentation and Incidence of Anaerobic Bacteria in Surgically Treated Biliary Tract Infections and Cholecystitis - Jens Strohäker; Lisa Wiegand; Christian Beltzer; Alfred Königsrainer; Ruth Ladurner; Anke Meier (MDPI AG, 2021)
(1) Background: Cholecystitis and cholangitis are among the most common diseases treated by general surgery. Gallstones lead to inflammation and bacterial infection of the biliary tract. Biliary infections can lead to live threatening bacteremia and liver abscesses. The true role of anaerobes remains unclear. (2) Methods: We retrospectively analyzed bacterial cultures from biliary samples obtained from bile ducts and gallbladders at our tertiary care center. Patient characteristics and clinical outcomes were analyzed. (3) Results: In our database of 1719 patients, 365 patients had microbial testing, of which 42 grew anaerobic bacteria. Anaerobes were more frequently cultured in patients with hepatic abscesses and gallbladder perforation. These patients were older and had more comorbidities than the control group. The overall outcomes of all patients were favorable and the resistance rate to commonly used antibiotics remained low. (4) Conclusions: Anaerobes in biliary tract infections appear to be underdiagnosed and more prevalent in the elderly with advanced disease. Due to low antibiotic resistance, the combination of source control and adjunct anti-infective treatment leads to favorable outcomes.